Comprehensive analysis of the aldehyde dehydrogenase gene family in Phaseolus vulgaris L. and their response to saline–alkali stress - Wang, Xiaoqin; Wu, Mingxu; Yu, Song; Zhai, Lingxia; Zhu, Xuetian; Yu, Lihe; Zhang, Yifei (Frontiers in Plant Science, 2024)
Background: Aldehyde dehydrogenase (ALDH) scavenges toxic aldehyde molecules by catalyzing the oxidation of aldehydes to carboxylic acids. Although ALDH gene family members in various plants have been extensively studied and were found to regulate plant response to abiotic stress, reports on ALDH genes in the common bean (Phaseolus vulgaris L.) are limited. In this study, we aimed to investigate the effects of neutral (NS) and basic alkaline (AS) stresses on growth, physiological and biochemical indices, and ALDH activity, ALDH gene expression of common bean. In addition,We used bioinformatics techniques to analyze the physical and chemical properties, phylogenetic relationships, gene replication, collinearity, cis-acting elements, gene structure, motifs, and protein structural characteristics of PvALDH family members. Results: We found that both NS and AS stresses weakened the photosynthetic performance of the leaves, induced oxidative stress, inhibited common bean growth, and enhanced the antioxidative system to scavenge reactive oxygen species. Furthermore, we our findings revealed that ALDH in the common bean actively responds to NS or AS stress by inducing the expression of PvALDH genes. In addition, using the established classification criteria and phylogenetic analysis, 27 PvALDHs were identified in the common bean genome, belonging to 10 ALDH families. The primary expansion mode of PvALDH genes was segmental duplication. Cis-acting elemental analysis showed that PvALDHs were associated with abiotic stress and phytohormonal responses. Gene expression analysis revealed that the PvALDH gene expression was tissue-specific. For instance, PvALDH3F1 and PvALDH3H1 were highly expressed in flower buds and flowers, respectively, whereas PvALDH3H2 and PvALDH2B4 were highly expressed in green mature pods and young pods, respectively. PvALDH22A1 and PvALDH11A2 were highly expressed in leaves and young trifoliates, respectively; PvALDH18B2 and